Molecular cloning and analysis of the scon-2 negative regulatory gene of Neurospora crassa. - Paietta, J V (1990)
The sulfur regulatory system of Neurospora crassa is composed of a group of highly regulated structural genes (e.g., the gene encoding arylsulfatase) that are under coordinate control of scon+ (sulfur controller) negative and cys-3+ positive regulatory genes. In scon-1 (previously designated sconC) and scon-2 mutants, there is constitutive expression of sulfur structural genes regardless of the sulfur level available to the cells. The scon-2+ gene was cloned by sib selection screening of a cosmid-based gene library. The screening was based on the use of chromate, a toxic sulfate analog, which is transported into scon-2 cells grown on high sulfur but is not transported into cells that have regained normal sulfur regulation. Restriction fragment length polymorphism analysis was used to confirm that the cloned segment mapped to the proper chromosomal location. In wild-type cells, Northern (RNA) blot analysis showed that a 2.6-kilobase scon-2+ transcript was present at a substantial level only under sulfur-derepressing conditions. Kinetic analysis showed that scon-2+ mRNA content increased as the cells became sulfur starved. Further, scon-2+ RNA was detectable in a nuclear transcription assay only under derepressing conditions. In scon-1, the levels of scon-2+ mRNA were found to be constitutive. In the cys-3 regulatory mutant, there was a reduced level of scon-2+ transcript. cys-3+ and ars-1+ mRNAs were present under both derepressing and repressing conditions in the scon-2 mutant. Repeat-induced point mutation-generated scon-2 mutants were identical in phenotype to the known mutant.